"What Is Computer-Mediated Communication?"—An Introduction to the Special Issue. Issue 1 (17th February 2020) - Yao, Mike Z; Ling, Rich
Abstract: At a time when nearly all social activities could be, and likely are, mediated in some ways by some forms of computing technology, what should be the focus of CMC research? How do we theorize and study computer-mediated (or should we say digitally-mediated) communication when the topics of our research—the technology, the concepts and processes of mediation, our sense of what constitutes communication, as well as the theories and methods used to examine these—are all in flux? Early in the spring of 2018, the Journal of Computer-Mediated Communication invited scholars to submit ideas for a dedicated issue to consider these questions. The collection of meta-theoretical discussions, literature reviews/analyses, and concept explications included in this special issue will point to a general direction and offer a launching point for theory construction and systematic research in a continuously evolving field.